Finite element investigation of knee joint analysis - Ho, Miao Ling (2016)
The knee joint is one of the most important parts of the human body. It is instrumental to almost every activity human beings take part in. As such, the understanding of the behaviour as well as the functions of each component in the knee joint is necessary to prevent any injury and to keep it healthy for as long as possible. It has been established that ACL is the most important ligament in the human knee and that one will not be able to perform their daily activities without it due to instability. This research paper looks into the significance of the ligaments in the knee joint using finite element study. The finite element knee joint model will first be validated through emulating experiments performed in journal studies and then comparing the results obtained. And secondly, analysis on the ligaments such as removing each ligament at a time, bearing the same loading and boundary conditions will be done to evaluate how much force will be exerted on the other ligaments with the absence of the respective ligament. This way, the significant of the missing ligament could be measured by the change in forces on other ligaments.